Psychosocial stress increases risk for type 2 diabetes in female cynomolgus macaques consuming a western diet. (May 2022) - Silverstein-Metzler, Marnie G.; Frye, Brett M.; Justice, Jamie N.; Clarkson, Thomas B.; Appt, Susan E.; Jeffrey Carr, J.; Register, Thomas C.; Albu-Shamah, Mays; Shaltout, Hossam A.; Shively, Carol A.
Abstract: Chronic psychosocial stress is associated with increased risk of many chronic diseases including type 2 diabetes mellitus. However, it is difficult to establish a causal relationship between stress and diabetes in human studies because stressors often are self-reported and may be distant in time from metabolic consequences. Macaques are useful models of the effects of chronic psychosocial stress on health and may develop obesity and diabetes similar to human beings. Thus, we studied the relationships between social subordination stress – a well-validated psychological stressor in macaques – and body composition and carbohydrate metabolism in socially housed, middle-aged female cynomolgus monkeys ( Macaca fascicularis ; n = 42). Following an 8-week baseline phase, the monkeys were fed a Western diet for 36 months (about equivalent to 10 human years). Social status was determined based on the outcomes of agonistic interactions ( X ¯ = 33.3 observation hours/monkey). Phenotypes collected included plasma cortisol, body composition, circulating markers of glucose metabolism, activity levels, and heart rate variability measured as RMSSD (root of mean square of successive differences) and SDDN (standard deviation of beat to beat interval) after 1.5- and 3-years on diet. Mixed model analyses of variance revealed that aggression received, submissions sent, and cortisol were higher, and RMSSD and SDNN were lower in subordinates than dominants (social status: p < 0.05). After 3 years of Western diet consumption, fasting triglyceride, glucose and insulin concentrations, calculated insulin resistance (HOMA-IR), body weight and body fat mass increased in all animals (time: all p's < 0.05); however, the increase in fasting glucose and HOMA-IR was significantly greater in subordinates than dominants (time x social status: p's < 0.05). Impaired glucose metabolism, (glucose > 100 mg/dl) incidence was significantly higher in subordinates (23%) than dominants (0%) (Fisher's exact test, p < 0.05). These findings suggest that chronic psychosocial stress, on a Western diet background, significantly increases type 2 diabetes risk in middle-aged female primates. Highlights: Chronic psychosocial stress significantly increased type 2 diabetes risk. Psychosocial stress may promote metabolic unhealthy obesity. Chronic psychosocial stress and western diet may impair parasympathetic activation.